Vapor-induced flow and its impact on powder entrainment in laser powder bed fusion - Li, Zhiyong; Yu, Gang; He, Xiuli; Gan, Zhengtao; Liu, Wing Kam (Elsevier, 2023)
A 2D axisymmetric transient Thermal-Fluid-Evaporation model coupled with melt pool dynamics and gas kinetics is developed to study the formation mechanisms of vapor-induced flow and the resulting powder entrainment in powder bed fusion using laser beam (PBF-LB) for 316 L powders. The interactions between keyhole formation inside the melt pool, vapor plume flow, and vapor-induced shielding gas flow are investigated. Vapor plume flow results in powder spattering with much higher speed, while vapor-induced gas flow significantly contributes to powder denudation with lower speed. It is also reported that powder spattering is stronger in 1 atm argon than that in 1 atm helium because the drag force for spattering is 2.72 times larger in 1 atm argon, but powder denudation becomes greater in 1 atm helium as the ratio of drag force for denudation in 1 atm argon to that in 1 atm helium is only 0.582. Furthermore, the vapor plume results in more spatters with the decrease of ambient pressure from 1 atm to 0.05 atm in argon because the plume is diluted faster with a twofold wider plume head and the two times higher peak velocity as a result of the pressure drop-induced significant reduction of viscosity restriction. A larger divergency angle in 0.05 atm argon is also recorded at the same time for the weaker restriction and faster dilusiton. In combination with in-situ observations, the proposed model provides insights into the vapor-induced flow, and its impact on powder entrainment under different gas types and ambient pressures.
Keywords: Numerical modeling; Powder spattering and denudation; 3D printing and additive manufacturing; Vapor plume flow; vapor-induced gas flow